The Pentrich Rebellion – a Nottingham affair? - Gaunt, Richard A. (Maney Publishers, 2018)
This article re-considers Nottingham’s role in the events immediately preceding the Pentrich Rebellion of 9-10 June 1817, as well as its reaction on the night of the Rebellion and during its aftermath. It does so in light of two continuing areas of historiographical debate: Nottingham’s status as a radical, potentially revolutionary, town, and the Rebellion’s links to Luddism. Nottingham loomed large in the planning and course of the Rebellion; it was heavily influenced by the work of a secret committee centred on Nottingham, the North Midlands Committee, which provided essential points of contact with the villages at the heart of the Rebellion. It was also a Rebellion led by a Nottingham man, Jeremiah Brandreth, ‘the Nottingham Captain’. However, the effective role played by Nottingham Corporation, in treading the fine line between revolution and reaction, the inability of the radicals to persuade would-be rebels that they had an effective plan, and the ability of the local magistrates and the Home Office to gather intelligence about the Rebellion, all worked against it. The chances of a successful reception in Nottingham were always much lower than the Rebels anticipated.